Expansion of frozen hybrids in the guppy ectoparasite, Gyrodactylus turnbulli. Issue 4 (4th January 2021) - Konczal, Mateusz; Przesmycka, Karolina J.; Mohammed, Ryan S.; Hahn, Christoph; Cable, Jo; Radwan, Jacek
Abstract: Hybridization is one of the major factors contributing to the emergence of highly successful parasites. Hybrid vigour can play an important role in this process, but subsequent rounds of recombination in the hybrid population may dilute its effects. Increased fitness of hybrids can, however, be frozen by asexual reproduction. Here, we identify invasion of a 'frozen hybrid' genotype in natural populations of Gyrodactylus turnbulli, a facultatively sexual ectoparasitic flatworm that causes significant damage to its fish host. We resequenced genomes of these parasites infecting guppies from six Trinidad and Tobago populations, and found surprisingly high discrepancy in genome‐wide nucleotide diversity between islands. The elevated heterozygosity on Tobago is maintained by predominantly clonal reproduction of hybrids formed from two diverged genomes. Hybridization has been followed by spread of the hybrids across the island, implying a selective advantage compared with native genotypes. Our results thus highlight that a single outcrossing event may be independently sufficient to cause pathogen expansion.